Antecedents of Employee Work Ethic; Human Relations and Organization Based Self Esteem - Wylda Kowey; Pieter NR Rehatta; Harvey Hiariey (Enrichment : Journal of Management, 2022)
This research was conducted based on the phenomenon at BPKP to provide suggestions regarding the problems faced by the personnel of the Maluku Province BPKP Representatives and to find out how much influence Human Relations and Organization Based Self Esteem had on the Work Ethic of the Maluku Province BPKP Representatives. The type of research used is quantitative research using primary data in the form of interviews, questionnaires and library research which is carried out systematically based on research objectives to BPKP employees of Maluku Province. The sample collection technique in this study used a saturated sample (non probability sampling), that is, all members of the population were used as samples. The results showed that the Human Relations and Organization Based Self Esteem variables had a significant influence on the work ethic of the Maluku Province BPKP Representative. The equation Y = 2.420 + 0.460X1 + 0.450X2 means that the Human Relations and Organization Based Self Esteem variables have a positive effect on work ethic. This study can be concluded that based on statistical tests (partial t test) all variables have a positive and significant influence on the work ethic variable and obtain an adjusted R value of 0.640. this shows that 64.0% work ethic is influenced by the two independent variables.